Technology with water, a discussion on sub-typology in industrial heritage according to world heritage sites - Shen, L; Asmawan Mohd Sarman; Mohamad Ibrahim Mohamad (Springer Nature, 2022)
Considering the diversity and complexity of cultural heritage, scholars pursue thematic study to trace specific categories, such as industrial heritage, to advance methodologies for better research, from which, sub-typologies were also introduced and proved as another efficient way. Technology decides the core value of industrial heritage, while water acts as an essential element in conformation and evolution of technology, which makes it as an perfect sub-type. So aiming to bring a new perspective for better research in industrial heritage, this article is driving a re-examination on the water-depend sites named on the World Heritage List (WHL) for identifying and discussing the new sub-type. It starts at the establishment of water-related group of the industrial heritage, followed by a series of attributes analysis compared with world cultural heritage from the criteria for inscription to the spatial structure and ends up with discussions about the recent global situation and acceptable subsequent strategies. Research results show that there is a regional centralization phenomenon which mainly reflects the geographical differences in achievements of technology and people’s consciousness on heritage conservation. The study also reveals that the sustainable use of water makes the new sub-type in industrial heritage possess potentiality to improve the unbalance in the value evaluation featured European-centric and can lead an important role in proceeding study on world cultural heritage under the Global Strategy. Holding the “outstanding universal value” and sticking to the “global strategy”, the study believes that catching up the sustainability of water-related industrial heritage, exploring the deep sub-typology of each category and using the place-narrative method to develop the environment of the remains can bring the bright future in this area with expansional apply to national or regional level. © 2022, The Author(s), under exclusive license to Springer Nature Switzerland AG.